Self Efficacy Terhadap Matematika Melalui Pendekatan Aptitude Treatment Interaction - Fitri, Irma (JURNAL REVIEW PEMBELAJARAN MATEMATIKA, 2017)
This study aims to determine differences in mathematics self-efficacy among students who learn to use the Aptitude Treatment Interaction (ATI) approach with students receiving conventional learning. This study is a quasi-experimental research, where teachers who play a direct role in the learning process and there researcher as an observer. Subjects in this study were 32 students on grade VIII SMP Negeri 2 Bangkinang Pekanbaru. Data collected by aptitude tests, observation, test result, and questionnaire. The result of this experiment indicated that self-efficacy scores students who learn using ATI approach and students receive conventional learning are different.